Methodology for functionalization of water oxidation catalyst IrOx nanoparticles with hydrophobic and multi-functionalized chromophores. Issue 60 (5th July 2021) - Fontana, Liniquer A.; Rigolin, Vitor H.; Braga, Carolyne B.; Ornelas, Catia; Megiatto, Jackson D.
Abstract : A straightforward "click" chemistry methodology for the sensitization of water soluble iridium oxide nanoparticles with hydrophobic and multi-functionalized porphyrin-based chromophores is described. Abstract : We present a straightforward "click chemistry" methodology for the functionalization of water-oxidation catalyst iridium oxide nanoparticles (IrO x -NPs) with a multi-functionalized porphyrin-based photosynthetic model as sensitizer for the preparation of bioinspired photo-catalysts. This efficient method overcomes the usual aggregation issue found when decorating water oxidation nanocolloidal catalysts with hydrophobic sensitizers.